Social Media Addiction among Nursing Students in College of Nursing, Spmvv, Tirupati - Mrs. U. Suhasini; Miss. Tiyari. Kalpana (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
INTRODUCTION Social media refers to the means of interactions among people in which they create, share, and/or exchange information It is a type of behavioural that is broadly defined as compulsive engagement it determined that the first users of social media are young population. College students are the vulnerable groups for the use of technology and social network. It develops new connections easily and relieves societal pressure OBJECTIVES: • To assess the social media addiction among nursing students. • To find out association between social media addiction and selected demographic variables among nursing students. • To suggest measures to prevent social media addiction. METHODOLOGY A descriptive research design was used to assess the level of social media addiction among nursing students in college of nursing, SPMVV, Tirupati. A total of 100 subjects were selected by using probability simple random sampling technique. RESULTS: The major findings of the study was among 100 nursing students 26 students had mild addiction, 58 students had moderate addiction and 16 students had severe addiction.. The results revealed that out of Correlation coefficient shows there was significant relationship between level of social media addiction and socio demographic variables ( P=0.05). CONCLUSION: Evidence from this investigation showed that the Majority of nursing students had moderate level of social media addiction. Hence there is necessity to have control over social media addiction among nursing students. Based on the obtained findings the researcher prepared a leaflet on suggest measures to prevent social media addiction.